FINITE ELEMENT ANALYSIS AND LIGHTWEIGHT OF FORKLIFT TRUCK WITH MAST SUBJECTED TO BENDING AND TORQUE MOMENT - LIU ZeChao; XU ZhiPei; WANG YuZhu; ZHANG KunMing (Jixie qiangdu, 2015)
This paper aims to study the forklift truck,which installs forklift in the middle section of a mast and creates the telescopic boom subjected to Bending and Torque Moment. FEA and Structure Optimization are carried out through ANSYS Workbench. Under the constraint conditions of size,strength,the stability against elastic buckling,and with board thickness and structure sizes as the design variables,disadvantageous working conditions are analyzed and optimized,all working conditions tested and verified,and optimal results and their rounds received under the goal of lightweight. This paper intends to find a way to fully realize the subjectivity to bending and torque moment,and lightweight design,and to work as reference for future lightweight design.